2014
DOI: 10.1039/c3nr05211g
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Rayleigh light scattering of single Au nanoparticles with different sizes and shapes

Abstract: Scientific interest in nanotechnology is driven by the unique and novel properties of nanometer-sized metallic materials such as the strong interaction between the conductive electrons of the nanoparticles and the incident light, caused by localized surface plasmon resonances (LSPRs). In this article, we analysed the relationship of the Rayleigh scattering properties of a single Au nanoparticle with its size, shape, and local dielectric environment. We also provided a detailed study on the refractive index sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…Another property of Au nanorods which ones should notice is that, if the aspect ratio of the Au nanorods is too large, the wavelength shift of the resonant Rayleigh light scattering spectrum will be higher than 800 nm after the adsorption or binding of biological materials, which is over the wavelength coverage of the micro-spectroscopy system. Therefore, the nanoparticle size and its spectral peak position must be selected with care to ensure sufficient signal intensity for LSPR assays [21,26]. These results indicate that the shape, size and aspect ratio of single Au nanoparticles determine the resonant Rayleigh light scattering properties such as the peak position, scatteringcross-section and the refractive index sensitivity, which gives a handle for the choice of Au nanoparticles for the design and fabrication of single Au nanoparticle sensors.…”
Section: Resonant Rayleigh Scatteringmentioning
confidence: 97%
See 3 more Smart Citations
“…Another property of Au nanorods which ones should notice is that, if the aspect ratio of the Au nanorods is too large, the wavelength shift of the resonant Rayleigh light scattering spectrum will be higher than 800 nm after the adsorption or binding of biological materials, which is over the wavelength coverage of the micro-spectroscopy system. Therefore, the nanoparticle size and its spectral peak position must be selected with care to ensure sufficient signal intensity for LSPR assays [21,26]. These results indicate that the shape, size and aspect ratio of single Au nanoparticles determine the resonant Rayleigh light scattering properties such as the peak position, scatteringcross-section and the refractive index sensitivity, which gives a handle for the choice of Au nanoparticles for the design and fabrication of single Au nanoparticle sensors.…”
Section: Resonant Rayleigh Scatteringmentioning
confidence: 97%
“…A deep understanding of the optical properties of noble nanoparticles allows one to develop practical applications [18,25]. Recently, Truong et al have analysed the relationship of the Rayleigh scattering properties of a single Au nanoparticle with its size, shape, aspect ratio and local dielectric environment by the dark-field micro-spectroscopy system [26]. They provided a detailed study on the refractive index sensitivity of three types of differently shaped Au nanoparticles, which were nanospheres, ovalshaped nanoparticles and nanorods.…”
Section: Resonant Rayleigh Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the size of gold nanoparticle (AuNP) has an unavoidable effect on the contact area between gold nanoparticle and biomolecules [28]. Thus, we had chosen a diameter of approximate 16 nm.…”
Section: Synthesis Of Gold Nanoparticlesmentioning
confidence: 99%